HYDRAULIC CHARACTERISTICS OF THE FIXED FREE SURFACE H-TYPE BREAKWATER SUBJECTED TO REGULAR WAVES - Wan Ismail, Wan Noor Afiq Afandy (IRC, 2015)
The destructive wave energy have bigger impacts on coastal line area and been challenge to many engineers and researchers. In addition, nowadays the coastal area are rapidly develop and call for new, effective, economic and environmental friendly coastal design, structure, management and engineering planning to protect from destructive wave energy. Thus, H-type breakwater are been proposed and suitable to be used because it is new breakwater designing in year of 2012, effective hydraulics performance based on previous physical modelling, cost effective and environmental friendly. The previous research of H-type breakwater by using mooring configuration have some limitation in wave attenuation. Therefore this research provide new information on new mounting system configuration with fixed-pile-supported structure to study the hydraulics performance of fixed H-type breakwater under regular waves by physical modelling. A series of 52 experiments were conducted with different wave periods, wave steepness, and wave height at water depth of 0.8 m, to study the hydraulic performance of fixed H-Type breakwater. The hydraulics performance of H-type model was evaluated and accessed based on wave transmission, wave reflection and wave attenuation using WAVELAB software. Laboratory tests confirmed that the fixed H-Type breakwater is a better wave attenuator and energy dissipater compared to the floating one